Tapak liman (Elephantopus scaber L) Extract Induced CD4+ and CD8+ Differentiation from Hematopoietic Stem Cell/Progenitor Cell Proliferation of Mice (Mus musculus) - Djati, M. Sasmito; Habibu, Hindun; Jatiatmaja, Nabilah A; Rifai, Muhaimin (The Journal of Experimental Life Science, 2015)
Tapak liman (Elephantopus scaber L) is one of the traditional medicinal plants, which are containing several active compounds that potentially affecting hematopoietic. The aims of this study are to elucidate the effect of leaf extract of Tapak Liman on hematopoietic in mice BALB/c, by observation on relative number of cells expressing CD4/CD8, CD4/CD62L, and TER119/B220 in the spleen; TER119/B220, TER119/VLA-4 and TER119/CD34 in bone marrow, after given the leaf extract for 2 weeks. This experiment was used 12 female mice, which is divided on 3group treated with leaf extract of Tapak Liman (P1= 0.5 g. g bw-1.day-1, P2= 1.0 g. g bw-1.day-1 and P3 = 2.0 g. g bw-1.day-1) and control. The relative numbers of cells expressing surface molecules were analyzed by flowcytometry and quantitative data were tested using one way ANOVA. The result showed the leaf extract of Tapak Liman has no significant effect on erythrocyte proliferation, on the other hand it have significant effect on both proliferation and differentiation of B lymphocytes (B220+) in the bone marrow (p=0.044) and increase the expression of CD4+, CD8+molecule in B cells (p=0.026) and erytroid (TER119+VLA-4+) in spleen and bone marrow. The administration of 1 g. g bw-1.day-1 of the extract (P2) stimulate proliferation of lymphocytes and erythrocytes lineage (TER119+VLA-4+), in spleen and bone marrow.Keywords: CD4+, CD8+, Elephantopus scaber, erythrocyte, hematopoiesis.